Impact of the Information Asymmetry Between Managers and Owners Under Oligopoly. (7th March 2016) - Brito, Duarte; Pereira, Pedro; Vareda, João
Abstract : We show, using a Hotelling (1929) model with Laffont and Tirole (1986) firms, that under duopoly, the information asymmetry caused by the separation of ownership and control has two effects on owners' incentives to induce effort. Information asymmetry raises the marginal cost of inducing effort, which decreases efforts and increases prices. Since all firms' prices increase, this leads to a change in the expected demand of each firm, and thus in the marginal benefit of inducing effort, which may amplify or mitigate the initial impact. As a consequence, information asymmetry may induce some firms to increase efforts and lower prices. More surprisingly, it may increase both ex post and ex ante social welfare.